Al Tafsir al kabir li al Imam al Fakhrurrazi - Fakharuddin Abu Abdillah Muhammad Husayn al_Fakhrurrazi (Dar al Kutub al 'Ilmiyyah)
ws.jl.1,2,4-7,,10,12-15,.c.1,jl.9.c.1-2/ stoc4=jil. 2=c.1-2, jil.1,jil.3-14; jil.25, c.1